Li/Zno And Chitosan/Li/Zno Quantum Dots For The Photocatalytic Oxidation Of Oxytetracycline - Jasni, Normawati (2023)
Quantum dots are a class of nano-sized materials that have the potential to be developed into photocatalysts due to their ability to absorb visible light, generate multiple excitons due to quantum confinement, have luminescent properties, and have a high surface-to-volume ratio. This study is divided into two parts. In the first part, Li/ZnO quantum dots (Li/ZnO QDs) was synthesized via microwave methods utilizing Li+ ion as capping agent. In the second part, the Li/ZnO QDs were encapsulated with chitosan (CHT/Li/ZnO QDs) to enhance the physicochemical properties of Li/ZnO QDs. The synthesised photocatalyst were characterised using Fourier-transform infrared (FT-IR) spectrometer, x-ray diffraction (XRD), high-resolution transmission electron microscope (HRTEM), scanning electron microscope (SEM), UV-vis diffuse reflectance spectroscopy (UV-DRS), photoluminescence (PL), nitrogen adsorption-desorption analysis (NAD) analysis, atomic force microscopy (AFM), x-ray photoelectron spectroscopy (XPS) and thermal stability (TGA). The SEM analysis shows that adding chitosan prevented the Li/ZnO QDs from agglomerating. The AFM analysis measured the surface roughness of Li/ZnO QDs and CHT/Li/ZnO QDs to be 21.7 to 33.2 nm, respectively. The increase is due to the ability of chitosan to form loosely packed smaller grains. The XRD analysis indicates that both photocatalysts contains hexagonal wurtzite type crystal structure.